D.W., the picky eater - Brown, Marc Tolon (Boston : Little, Brown, 1995)
Because her eating habits cause some problems, Arthur the aardvark's younger sister has to stay home when her family eats out.
1 3 4 7 13 15 18 21 26 27 29 30 34 38 39
Keywords: Food habits -- Fiction; Aardvark -- Fiction